2016
DOI: 10.1097/iae.0000000000001289
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Cystoid Spaces in Chronic Diabetic Macular Edema and Capillary Nonperfusion Detected by Optical Coherence Tomography Angiography

Abstract: In chronic DCME, cystoid spaces were located within capillary dropout areas. No reperfusion occurred after DCME resolution. The impact of the severity of this nonperfusion on the risk of recurrence of DCME remains to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 19 publications
6
68
3
Order By: Relevance
“…In contrast, Spaide et al 40 showed that anti-VEGF therapy results in resolution of edema without changes in the nonperfusion area. Mané et al 41 have also indicated that anti-VEGFassociated reperfusion is unlikely to occur but the capillaries already present above the cystoid spaces became visible in eyes with resolved DME. Based on the current study, we speculate that in eyes with macular edema with well-established areas of capillary dropout before treatment, the retinal capillaries may not return even after resolution of the edema.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Spaide et al 40 showed that anti-VEGF therapy results in resolution of edema without changes in the nonperfusion area. Mané et al 41 have also indicated that anti-VEGFassociated reperfusion is unlikely to occur but the capillaries already present above the cystoid spaces became visible in eyes with resolved DME. Based on the current study, we speculate that in eyes with macular edema with well-established areas of capillary dropout before treatment, the retinal capillaries may not return even after resolution of the edema.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also suggest that OCTA parameter alterations in the deep vascular layer are affected more severely than in the superficial vascular layer in NPDR [10, 11, 14-16, 17, 21, 23, 26]. OCTA parameters at the deep vascular layer were most significantly affected in patients with DME [4, 29-32]. …”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In a study involving patients with DME, all cases had lost the regular vascular pattern in the deep vascular layer [29]. Decorrelation signal-void areas around intraretinal cystoid spaces were present in 71% of the cases in the superficial vascular layer and in 96% of the cases in the deep vascular layer.…”
Section: Octa Parameters In the Superficial Deep And/or Intermediatmentioning
confidence: 99%
“…26,27 Capillary density of both plexuses is correlated to visual loss in diabetic retinopathy, 28 branch retinal vein occlusion, 29,30 and idiopathic macular telangiectasia type 1 (MacTel1). 31 In addition, several investigators have shown that decreased perfusion is more frequent in the deep than superficial plexus, in central or branch vein occlusion, 32-34 diabetic retinopathy, 35 and MacTel1. 36 In resolved branch retinal vein occlusion, deep plexus nonperfusion has recently been identified as a more critical determinant of BCVA than superficial plexus nonperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…36 Deep plexus disruption could also result from tissue displacement by cystoid edema cavities, but the possibility of small interconnected capillaries forming this plexus to be stretched by edema is unlikely. 35,36 Finally, it could also result from shadowing or edema-related signal artifacts. 33,36,37 Here, the causal relationship between edema formation and deep plexus alteration was possibly indicated by the stronger correlation of CMT (and CMT change) with deep plexus changes, assessed by grading, vascular density, and local fractal dimension, than with superficial plexus changes (see Table 4).…”
Section: Discussionmentioning
confidence: 99%